Occurrence and Pathways of Microplastics, Quantification Protocol and Adverse Effects of Microplastics Towards Freshwater and Seawater Biota - Yahya, H.; Karim, S.N.; Yahaya, N.; Syed Abd Halim, S.A.S.; Zanuari, F.I.; Yahya, H.N. (Rynnye Lyan Resources, 2024)
Indexed by Scopus/MyCite